Removal of heavy metals using bacterial bio-flocculants of Bacillus sp. and Pseudomonas sp. - M. Azzam, Ahmed; Tawfik, Ahmed (Journal of Environmental Engineering and Landscape Management, 2015)
Bio-flocculants produced by Bacillus sp. and Pseudomonas sp. were evaluated as flocculating agents for the removal of Cu (II), Pb (II) and Cd (II) from chemical and textile wastewater industries. Both bio-flocculants were very effective for removal of heavy metals at a dosage not exceeding 0.1 mg/ml. However, the removal efficiency of heavy metals was dependant on initial concentration and type of bio-flocculants. 84.0% of Cu2+ and 99.5% of Pb2+ were removed from industrial wastewater using Bacillus sp. Bio-flocculant resulting residual values of 28.5 and 1.13μg/l respectively in the treated effluent. Lower removal efficiencies of 70.4% for Cu2+ and 97.8% for Pb2+ occurred using Pseudomonas sp. bioflocculant. Nevertheless, Pseudomonas sp. bio-flocculant achieved a substantially higher removal efficiency of Cd2+ (93.5%) as compared to 72.9% using Bacillus sp. Based on these results bio-flocculants are considered as a viable alternative for the treatment of industrial wastewater containing heavy metals.First published online: 27 Oct 2015